Bedah Buku dan Diskusi Ilmiah Ala Gen Z bersama Dosen Fakultas Hukum Universitas Lampung. Literasi untuk Negeri: “Buku Bukan Buat Nugas Doang” - Rahman, Rafika Rizky Aulia; Malida, Reisa; Yanis, Adam Muhammad (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2025)
The issue of low reading interest in Indonesia remains a complex challenge, not only related to illiteracy rates but also involving broader cultural and structural aspects. In the context of legal education, weak literacy culture can hinder the development of critical thinking and legal imagination, both essential for addressing contemporary legal challenges. This community engagement activity aims to foster reading interest among law students through a literacy approach that goes beyond legal documents, incorporating fiction and other multidisciplinary readings. Through training and discussion sessions involving law students in Bandar Lampung, this activity identifies factors influencing reading habits and encourages participants to be more critical in selecting credible reading sources. The results indicate a gap between academic reading obligations and personal reading motivation. Therefore, a contextual and creative literacy approach is needed to shape law students who are not only capable of reading legal documents but also possess interdisciplinary insight, empathy, and strong legal imagination. Keywords: Book Review, Fiction, Law, Literacy